Gingival and alveolar ridge tumor-like overgrowth lesions - Salwan Y H Bede (College of Dentistry/ University of Baghdad, 2014)
Background: Tumor-like overgrowth lesions of the oral mucosa are pathological growths that project above the normal contour of the oral surface. A practical classification can be made according to the site of origin, the etiology and the histological appearance. The aim of this article is to evaluate and analyze patients with gingival and alveolar ridge tumor-like overgrowth lesions in terms of surgical treatment, diagnosis and outcome. Materials and Methods: Patients complaining of these lesions were treated by surgical excision under local or general anesthesia; the excised lesions were submitted for histopathological examination, during the follow up period the patients were examined for complications and recurrence. Results: Pyogenic granuloma was the most frequently encountered lesion, followed by peripheral giant cell granuloma, fibrous hyperplasia, peripheral ossifying fibroma and neurofibroma. Complications were minimal and recurrence occurred in one patient. Conclusion: Gingival and alveolar ridge overgrowths are common being mostly reactive rather than neoplastic in nature, global recurrence rate was 2.1%.